Matematično modeliranje talilnega učinka pri varjenju z dvojno žično elektrodo pod praškom - Tušek, Janez (Kovine zlitine tehnologije, 1995)
In arc welding with consumable electrode, two principles of mathematical predicition and calculation of the quantity of filler molten material have asserted themselves. The first one is statistical method, the second is based on physical principles, on metallurgical, physical and chemical properties of material used in welding. In the present article both methods will be used to elaborate a model of melting rate. Two mathematical models for submerged arc welding with twin-wire electrode with electrode negative and electrode positive resp. are presented. With reference to known world technical literature, these are probably the first models for calculating of melting rate in welding with twin-wire electrode.
Keywords: varjenje; varjenje pod praškom; talilni učinek; dodajni materiali; matematični modeli